Synthesis of polyurethane incorporated by calcium oxide and magnesium oxide for heavy metal removal from water / Mohsen Vafaei Fard - Mohsen Vafaei , Fard (2020)
Water contaminated by heavy metals such as copper, lead, nickel, and cadmium has significant adverse impacts on receiving water. In recent years, various methods, such as adsorption, chemical precipitation, and ion exchange, have been extensively studied for the elimination of heavy metals. Adsorption is one of the numerously and diversely reported mechanisms of removing heavy metals due to its simplicity and costeffectiveness. In this study, highly permeable rigid polyurethanes (PU) incorporating calcium oxide (CaO) (PU/CaO) composite materials were prepared via a facile and economic one-pot synthesis method and characterized for remediation of heavy metal from water. To investigate the effect of CaO on heavy metal adsorption, the amount of CaO was varied from 0 to 25 of total weight (wt.%) of polyol and Methylene diphenyl diisocyanate (MDI). Among the media tested, 25% CaO-incorporated PU (PU/CaO-25) had the highest adsorption capacity (Qmax = 35.6 mg.g-1) of Cu(II). The PU/CaO-25 is capable of removing Cu(II), Pb(II), Zn(II), and Ni(II) ions by both adsorption and ion exchange mechanisms. However, precipitation was the dominant mechanism for removal of metal ions due to the increase of pH in the solutions. Moreover, column tests were conducted to investigate various parameters, and data were interpreted using the Bed Depth Service Time (BDST) model to predict service time. Specific structural features of PU/CaO-25 and the remediation mechanism were also determined using FESEM/EDS, XRD, N2 gas isotherm, and chemical equilibrium modeling. Moreover, column tests using simulated urban storm-water runoff (USR) showed that PU/CaO-25 removed all heavy metals such as Cu(II), Zn(II), Ni(II), and Pb(II) to below their regulation levels at~1,100-bed volumes (BVs). In the second stage of this research to enhance the removal efficiency of heavy metals by using PU, commercial MgO was used, and a simple hydrothermal method was applied to the mixture of commercial MgO and granular PU (gPU). Three-dimensional (3D) flowerlike Mg(OH)2 structures (FMH) were built on the surface of gPU (gPU-FMH). Hydrothermal process and gPU was the key factors for the assembly of the FMH. The synthesized hexagonal nanosheet petals of gPU-FMH provided a high surface area. The gPU-FMH showed the superb adsorption capacity (Qmax = 472, 1050, and 1293 mg.g-1 for Cu(II), Cd(II), and Pb(II), respectively). The proposed hypothesis for the synthesis of gPU-FMH and the removal mechanism of the heavy metals has been proved through various spectroscopic analyses. It was found that Mg(OH)2 dissociation in the metal solution produces two OH- ions that subsequently react with the metal ions. Based on the stoichiometry, this reaction can render the production of insoluble precipitates through coupling with the anionic species that exist in the solution. Further, the precipitates will become trapped in the gaps of the FMH particles, and the precipitation might be the dominant removal mechanism at the higher metal-ion concentrations. In the results of the continuous-flow column study, gPU-FMH showed a much higher removal capacity (184 mg.g-1) of Cu(II) than the other referenced media.